DNA Repair Syndromes and Cancer: Insights Into Genetics and Phenotype Patterns - Sharma, Richa; Lewis, Sara; Wlodarski, Marcin W. (Frontiers in Pediatrics, 2020)
DNA damage response is essential to human physiology. A broad spectrum of pathologies are displayed by individuals carrying monoallelic or biallelic loss of function mutations in DNA damage repair genes. DNA repair syndromes with biallelic disturbance of essential DNA damage response pathways manifest early in life with multi-systemic involvement and a high propensity for hematologic and solid cancers, as well as, bone marrow failure. In this review, we describe classic biallelic DNA repair cancer syndromes arising from faulty single and double strand DNA break repair, as well as dysfunctional DNA helicases. These clinical entities include xeroderma pigmentosum, constitutional mismatch repair deficiency, ataxia telangiectasia, Nijmegen breakage syndrome, deficiencies of DNA ligase IV, NHEJ/Cernunnos, and ERCC6L2, as well as Bloom, Werner, and Rothmund-Thompson syndromes. To give an in-depth understanding of these disorders, we provide historical overview and discuss the interplay between complex biology and heterogeneous clinical manifestations.